Analisis Spasial Perubahan Fragmentasi Hutan pada Kawasan Penyangga di Cagar Alam Maninjau - Azzakia, Habib; Frananda, Hendry (TSAQOFAH, 2025)
Forest fragmentation poses a significant threat to ecosystem sustainability, particularly in buffer zones that function to protect the core of conservation habitats. This study aims to analyze forest fragmentation changes in the Buffer Zone of the Maninjau Nature Reserve during the period 2006–2024 and to identify their driving factors. Landsat TM 5 and OLI 8 satellite imagery were processed using the Random Forest method on Google Earth Engine. Fragmentation analysis was conducted through landscape indices (Landscape Shape Index [LSI], Number of Patches [NP], Patch Density [PD], Edge Density [ED]) using the landscapemetrics packages in R Studio and Fragmentation using GIS Tools v2 in ArcGIS. Driving factors were examined within the Driving forces–Pressures–State–Impacts–Responses (DPSIR) framework, focusing on population growth and agricultural land expansion. The results reveal a significant decline in LSI, NP, PD, and ED values in edge areas, indicating habitat loss and the subdivision of forests into smaller patches. The reduction in large core areas in mountainous regions reflects consistent agricultural expansion over the years. Fragmentation transition analysis confirms the continuous loss of forest cover, particularly in edge zones. Key driving factors include population growth, which increases the demand for residential land, and extensive agricultural expansion, particularly oil palm plantations that converts forests into degraded lands. These findings highlight the importance of integrated landscape management to reduce deforestation and maintain the ecological functions of buffer zones.